(untitled) (Research, Society and Development, 2021)
The use of social networks in education was reinforced by the particularity of the context created by the COVID-19 pandemic, and these tools contribute to the engagement and interaction of students, as well as facilitating communication between teacher and student. From this perspective, this work aims to report the experience of using social networks as pedagogical tools; present the advantages and difficulties of working with social networks in basic education and point out social networks as a space for communication, interaction and training. With this in mind, a brief review of the theme was carried out first, followed by a discussion of an experience report on the use of social networks in an educational path. It is concluded that social networks proved to be an important didactic and pedagogical resource in basic education, constituting a space for interdisciplinary training and skills development.